Prevalence and profile of headache in school-going adolescents aged 10 – 19 years in Benin City: a cross sectional survey - Ikhurionan, Paul; Mbarie, Imuwahen (Headache Medicine, 2024)
Introduction Adolescent headaches significantly impact their daily functioning, academic performance, and quality of life. The occurrence of headaches is influenced by genetics, psychological stressors, and environmental exposures. Understanding these influences is crucial for effective management strategies. Aim To determine the prevalence, characteristics, and associated factors of headaches among school-going adolescents in Benin City, Nigeria. Methods This was a descriptive cross-sectional study among secondary school students. Using a structured questionnaire, data on sociodemographics, headache characteristics, triggers, and impacts were collected. The chi-square test was used to assess the association between the presence of headaches and categorical covariates. All analyses used a significance level of p<0.05. Result Of the 486 respondents 235 (48.4%) were boys and 251 (48.3%) were girls with a M:F ratio of 1:1.07. The mean age of the study participant was 13.7 (+ 1.78) years. The one-year prevalence of headache was 84%. 92 (18.9%) of those reporting headaches met the diagnostic criteria for chronic daily headache. The most common impact of headache was poor concentration (110; 22.6%). Psychological stress (55.3%) and poor sleep (26.1%) were the most commonly reported headache triggers. Conclusion More than four in five school-going adolescents have headache at one time in the past year. Reading and concentration problems are the most common adverse effect of headache in adolescents.